2021
DOI: 10.17159/wsa/2021.v47.i1.9447
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of the mid-summer dry spells for the summer rainfall region of South Africa

Abstract: South Africa is frequently subjected to severe droughts and dry spells during the rainy season. As such, rainfall is one of the most significant factors limiting dryland crop production in South Africa. The mid-summer period is particularly important for agriculture since a lack of rain during this period negatively affects crop yields. Dry spell frequency analyses are used to investigate the impacts of sub-seasonal rainfall variability on crop yield, since seasonal rainfall totals alone do not explain the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The majority of the savanna biome's global distribution has highly variable rainfall, both within and across years, and this variability is predicted to increase with climate change (Krishna Prabhakar, 2022). Studies across the globe (Jacob et al ., 2014; Singh et al ., 2014; Marengo et al ., 2016; Breinl et al ., 2020), including Africa (Usman & Reason, 2004; MacKellar et al ., 2014; Mengistu et al ., 2021), have shown a decrease in the number of rainy days and an increase in the frequency of growing season dry spells. While the mechanisms of how prerain green‐up provides an opportunity for trees to grow without competition from grasses (temporal niche separation) and contributes to tree–grass coexistence have been relatively well documented in savannas (Scholes & Walker, 2004; Higgins et al ., 2011; Holdo & Nippert, 2023), only a few studies have explored how tree–grass interactions are likely to be affected by the increased variability in rainfall patterns expected with climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the savanna biome's global distribution has highly variable rainfall, both within and across years, and this variability is predicted to increase with climate change (Krishna Prabhakar, 2022). Studies across the globe (Jacob et al ., 2014; Singh et al ., 2014; Marengo et al ., 2016; Breinl et al ., 2020), including Africa (Usman & Reason, 2004; MacKellar et al ., 2014; Mengistu et al ., 2021), have shown a decrease in the number of rainy days and an increase in the frequency of growing season dry spells. While the mechanisms of how prerain green‐up provides an opportunity for trees to grow without competition from grasses (temporal niche separation) and contributes to tree–grass coexistence have been relatively well documented in savannas (Scholes & Walker, 2004; Higgins et al ., 2011; Holdo & Nippert, 2023), only a few studies have explored how tree–grass interactions are likely to be affected by the increased variability in rainfall patterns expected with climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The end of the wet season was defined as the date after the start of the wet season when no rain occurred for a period of 20 consecutive days following (Zhang et al, 2005;Adole et al, 2018). Mengistu et al (2021) and Usman & Reason (2004) have previously analysed how mid-growing season dry spells are likely to affect the dryland production of maize in the summer rainfall parts of Southern Africa using pentad analyses. We suggest that savanna vegetation, especially the grass component, should be similar to maize in their response to rainfall patterns and have therefore adopted their approach and defined a dry spell as a period of 5 d (a pentad) during which rainfall totals were < 5 mm.…”
Section: Analyses Of Long-term Rainfall Recordsmentioning
confidence: 99%
“…We also found that 17 (32%) studies assessed the frequency of drought [24,45,61,69,76,80,127]. It was possible to identify in the documents that the assessed drought classes were severe/extreme drought with 15 (28%) studies [44,45,51,68,70,76,127] and 7 (13%) for severe/moderate drought [24,33,53,55,58,70,128]. However, none of the documents reports a complete study of the drought regime or the spatial and temporal distribution of all drought descriptors.…”
Section: Drought Descriptorsmentioning
confidence: 91%
“…Farmers are seeing an increase in the frequency of dry spells and droughts during the summer. These dry spells are described as long stretches of time without rain during the rainy season [13,14]. The amount of water available is also impacted by differences in rainfall, which raises temperatures, especially on hot days when most farmers in the area rely on rainfall for irrigation.…”
Section: Introductionmentioning
confidence: 99%